Evaluation of Waiting Time for BPJS Patient Prescription Services from the Perspective of Human Resource Management and Operational Processes: Study at the Outpatient Pharmacy Depot of RSUD X, Sorong Regency - Batjo, Iriyanti; Yaniawati, R. Poppy; Widjaja, Yani Restiani (Business Management, 2026)
Prescription waiting time is a key indicator of pharmacy service quality that directly affects patient satisfaction and overall perceptions of hospital performance. In public hospitals, particularly among BPJS patients who dominate outpatient visits, achieving efficient waiting times remains a challenge due to workforce limitations and operational constraints. This study aims to evaluate prescription waiting time for BPJS patients and analyze the influence of human resource management (HRM) and operational processes on service efficiency at the Outpatient Pharmacy of RSUD X, Sorong Regency. This research employed a mixed-method approach with a sequential explanatory design. The study population included all pharmacy personnel and BPJS outpatient prescriptions. The quantitative phase involved five pharmacy staff selected through total sampling and 336 BPJS prescriptions obtained from a population of 2,100 prescriptions using the Slovin formula (5% margin of error) and simple random sampling. The qualitative phase included six key informants purposively selected based on their strategic roles in drug logistics, prescription services, and pharmacy operations. The results showed that prescription waiting time exceeded the minimum service standards. HRM factors including workload-based staffing, performance evaluation, and compensation systems significantly influenced service speed. Operational factors such as drug availability, use of e-prescriptions, adherence to SOPs, and compliance with the hospital formulary also demonstrated significant effects. Simultaneously, both HRM and operational processes significantly affected waiting time, with HRM identified as the dominant factor. The study concludes that prescription waiting time for BPJS patients at the Outpatient Pharmacy of RSUD X Sorong Regency has not met the minimum service standards due to HRM and operational constraints.